PERANAN KOMUNIKASI DALAM INTERAKSI BUDAYA - Wahyuni Husain (IAIN Palopo, 2010)
This paper focused on the important of communication in people interaction with background culture are different. Intercultural communication is very infortant because there are mobility to cause interaction people with culture that heterogenity and also developmental information technology that quickly